2004
DOI: 10.1111/j.1365-2702.2004.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

District nursing – sharing an understanding by being present. Experiences of encounters with people with serious chronic illness and their close relatives in their homes

Abstract: This study reveals the need to be entirely present in encounters between the district nurses and people with serious chronic illness and their close relatives. This relation makes it possible to establish a shared understanding of the illness experience. Being aware of the importance of this shared understanding within a relationship, will increase the health care personnel's possibility to alleviate and console those suffering of illness. This proposed interpretation could be useful for reflection of care int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…District Nurses (DNs) visit patients with advanced cancer early in the dying trajectory to support them and their families, and build a relationship before hands-on, intimate care is needed at the end of life (Seale, 1992;Austin et al, 2000;Mok and Chui, 2004;Ohman and Sodreberg, 2004;Coffey, 2006;Stolz et al, 2006: FingfeldConnett, 2007. DNs are confident and skilled in providing practical support and physical care (Griffiths et al, 2012) and are ideally placed to identify and respond to psychological concerns Pateman, 2003;Kennedy, 2005;Griffiths et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…District Nurses (DNs) visit patients with advanced cancer early in the dying trajectory to support them and their families, and build a relationship before hands-on, intimate care is needed at the end of life (Seale, 1992;Austin et al, 2000;Mok and Chui, 2004;Ohman and Sodreberg, 2004;Coffey, 2006;Stolz et al, 2006: FingfeldConnett, 2007. DNs are confident and skilled in providing practical support and physical care (Griffiths et al, 2012) and are ideally placed to identify and respond to psychological concerns Pateman, 2003;Kennedy, 2005;Griffiths et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses perceive their caring role as showing respect for all kinds of people, described as human love. Öhman and Söderberg stated that it is difficult for community nurses to emotionally distance themselves when caring for end‐of‐life patients in the latter's own home . Furthermore, Karlsson and Berggren found that the actions of nursing staff are of the utmost importance for a good outcome of end‐of‐life care in the patient's own home.…”
Section: Introductionmentioning
confidence: 99%
“…2000, McNaughton 2000, Jansson et al. 2001, Kennedy 2002b, Crisp & Lister 2004, Ohman & Soderberg 2004).…”
Section: Resultsmentioning
confidence: 99%